PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. ATA INTERNASIONAL INDUSTRI - Dunggio, Maryam; Sukatmadjaya, Ahmad; Habib, Mughni (Kinerja, 2021)
This study aims to prove the effect of compensation and work environment on employee productivity at PT. ATA International Industri. The research was conducted on production employees. The number of samples used in this research was 90 employees. This research uses analysis with the SEM-PLS model. The results of the research prove that the compensation given properly and by the agreed terms has a positive and significant effect on employee productivity. In addition, the results of this research prove that a good and comfortable work environment has a positive and significant effect on employee productivity.